Differential secretome analysis of cancer‐associated fibroblasts and bone marrow‐derived precursors to identify microenvironmental regulators of colon cancer progression. Issue 2 (6th January 2013) - De Boeck, Astrid; Hendrix, An; Maynard, Dawn; Van Bockstal, Mieke; Daniëls, Annick; Pauwels, Patrick; Gespach, Christian; Bracke, Marc; De Wever, Olivier; Wu, Fang‐Xiang; Ressom, Habtom; Dunn, Michael J.
<x xml:space="preserve">Abstract</x> The identification of cancer‐associated fibroblast (CAF)‐derived proteins that mediate interactions between the tumor stroma and cancer cells is a crucial step toward the discovery of new molecular targets for therapy or molecular signatures that improve tumor classification and predict clinical outcome. CAF are α‐smooth muscle actin positive, representing a myofibroblast phenotype that may differentiate from multiple precursor cells, including bone marrow‐derived mesenchymal stem cells (MSC). Transforming growth factor‐β1 (TGF‐β1) is a crucial inducer of α‐smooth muscle actin positive CAFs. In this study, we aimed to identify CAF‐derived regulators of colon cancer progression by performing a high‐throughput differential secretome profiling between CAF compared to noncancer‐activated bone marrow‐derived MSC. In addition, we explored the effect of TGF‐β1 on the secretion of proteins by bone marrow‐derived MSC in comparison with the protein secretion profile of CAF. TGF‐β1 induced de novo secretion of 84 proteins in MSC, of which 16 proteins, including stromal‐derived factor‐1α and Rantes, were also present in CAF secretome. Immunohistochemistry further validated the expression of selected candidates such as tenascin C, fibronectin ED‐A domain and stromal‐derived factor‐1 in clinical colon cancer specimens. In conclusion, this differential secretome approach enabled us to identify a series of candidate biomarkers for colon cancer that are associated with a CAF‐specific phenotype.